The effect of instructional embodiment designs on Chinese language learning: The use of embodied animation for beginning learners of Chinese characters - Lu, Ming-Tsan Pierre (ProQuest Dissertations & Theses, 2011)
The focus of this study was an investigation of the effects of embodied animation on the retention outcomes of Chinese character learning (CCL) for beginning learners of Chinese as a Foreign Language (CFL). Chinese characters have three main features: semantic meaning, pronunciation, and written form. Chinese characters are different from English words in that they are non-alphabetic orthographies. Though popular, they are deemed very hard to learn. However, Chinese character processing is found to be neurologically related to human body movements, or at least the imagination of them. Literature also indicated the importance of embodied cognition, imagination, and technology use in human language memory and learning. The design of embodied animation for a computer-based CCL program is developed which consists of three types of characters. The study used Between-Subject Post-test Only Control Group experimental design with sixty-nine adults. The study compared five learning conditions: embodied animation learning (EAL), human-image animation learning (HAL), object-image animation learning, no-animation etymology learning, and traditional learning (serving as a control group). Participants in the EAL group perceived the character etymological animation, and then a video clip depicting the moving actions of human body movements and/or gestures which show the semantic meaning and the written form of the character. The study found that the EAL group outperformed the other learning groups with medium to large effects. Specifically, after one week of learning, the EAL group outperformed the other groups in terms of learners' free recall of Chinese characters, in characters' meaning-form mappings, and in characters' form-meaning and-sound mappings. Furthermore, the EAL group performed better than the other groups in the retention of all three types of characters (i.e., pictograph, indicative, and ideograph). Therefore, findings revealed the positive effects of embodied animation on CCL. In addition, the HAL group showed promising retention rate by constantly performing the second best in all tasks. The study also revealed that pictographs and indicatives were better learned than ideographs across groups. Drawing from the study, the use of embodied animation in a computer-based program is suggested to be effective on character learning for beginning learners of CFL.